(untitled) (Philadelphia, 1994)
This manual provides practical information on how to manage medical diseases and conditions most frequently encountered in medical wards and emergency departments. It should help to solve on-call problems and provides a bedside approach with advice on relevant investigations and full discussions of drug and interventional therapy that is equivalent to coverage in large volume texts on current therapy. The manual is written by clinical professors and clinical teachers who have had considerable practice in medical wards. Topics covered include cardiovascular, pulmonary, rheumatology, endocrinology, gastroenterology, haematology and infectious diseases. Conditions not requiring hospitalization or emergency room management are therefore omitted.
Keywords: Nội khoa,Internal medicine